Barx2 and Pax7 Have Antagonistic Functions in Regulation of Wnt Signaling and Satellite Cell Differentiation. (23rd May 2014) - Zhuang, Lizhe; Hulin, Julie-Ann; Gromova, Anastasia; Tran Nguyen, Thi Diem; Yu, Ruth T.; Liddle, Christopher; Downes, Michael; Evans, Ronald M.; Makarenkova, Helen P.; Meech, Robyn
Abstract: The canonical Wnt signaling pathway is critical for myogenesis and can induce muscle progenitors to switch from proliferation to differentiation; how Wnt signals integrate with muscle-specific regulatory factors in this process is poorly understood. We previously demonstrated that the Barx2 homeobox protein promotes differentiation in cooperation with the muscle regulatory factor (MRF) MyoD. Pax7, another important muscle homeobox factor, represses differentiation. We now identify Barx2, MyoD, and Pax7 as novel components of the Wnt effector complex, providing a new molecular pathway for regulation of muscle progenitor differentiation. Canonical Wnt signaling induces Barx2 expression in muscle progenitors and perturbation of Barx2 leads to misregulation of Wnt target genes. Barx2 activates two endogenous Wnt target promoters as well as the Wnt reporter gene TOPflash, the latter synergistically with MyoD. Moreover, Barx2 interacts with the core Wnt effectors β -catenin and T cell-factor 4 (TCF4), is recruited to TCF/lymphoid enhancer factor sites, and promotes recruitment of β -catenin. In contrast, Pax7 represses the Wnt reporter gene and antagonizes the activating effect of Barx2. Pax7 also binds β -catenin suggesting that Barx2 and Pax7 may compete for interaction with the core Wnt effector complex. Overall, the data show for the first time that Barx2, Pax7, and MRFs can act as direct transcriptional effectors of Wnt signals in myoblasts and that Barx2 and Wnt signaling participate in a regulatory loop. We propose that antagonism between Barx2 and Pax7 in regulation of Wnt signaling may help mediate the switch from myoblast proliferation to differentiation. Stem Cells   2014;32:1661–1673